Development of E-LKPD (Electronic Leaner Worksheet) Based on Project Based Learning for Lathe Machining Engineering Subjects - Adi Firman Romadhon; Eddy Sutadji (VANOS Journal of Mechanical Engineering Education, 2026)
This study aims to develop and test the feasibility of Project Based Learning (PjBL)-based E-LKPD in the subject of Lathe Machining to improve the quality of practice of grade 11 vocational school students. The main problem raised is the low motivation and limitations of conventional print media in supporting interactive learning. Using the Research and Development (R&D) method, data was collected through expert validation and response questionnaires for 34 students and teachers. The results of the study show that E-LKPD is very feasible and valid with an average percentage of 80.88% (material) and 77.27% (media). This product is considered very complete (90.00%) and practical (85.48%) as a learning resource. The implementation of media has been proven to significantly increase students' learning motivation (90.20%) and provide convenience for teachers in delivering material (90.00%). It was concluded that PjBL-based E-LKPD is effectively used to optimize the technical learning process in vocational schools. Keywords: Interactive E-LKPD, Project Based Learning, Lathe Machining Techniques, Quality of Vocational Practice Practices, Digital Learning Media.